Molecular identification, antifungal susceptibility, and resistance mechanisms of pathogenic yeasts from the China antifungal resistance surveillance trial (CARST-fungi) study - Wang, Qiqi; Cai, Xuan; Li, Yun; Zhao, Jianhong; Liu, Zhiyong; Jiang, Yan; Meng, Ling; Li, Yanming; Pan, Shiyang; Ai, Xiaoman; Zhang, Fang; Li, Ruoyu; et al. (Frontiers in Microbiology, 2022)
To have a comprehensive understanding of epidemiology and antifungal susceptibilities in pathogenic yeasts, the China Antifungal Resistance Surveillance Trial (CARST-fungi) study was conducted. All yeast isolates were identified by ribosomal DNA sequencing. Antifungal susceptibilities were performed using CLSI M27-A4 broth microdilution method. Sequence and expression level of resistant-related genes in resistant/non-wide-type (NWT) Candida isolates were analyzed. Totally 269 nonduplicate yeast isolates from 261 patients were collected. About half of the yeast isolates (127, 47.2%) were recovered from blood, followed by ascetic fluid (46, 17.1%). C. albicans remained the most prevalent (120, 44.6%), followed by C. parapsilosis complex (50, 18.6%), C. tropicalis (40, 14.9%), and C. glabrata (36, 13.4%). Fourteen (11.7%) C. albicans isolates and 1 (2.0%) C. parapsilosis isolate were resistant/NWT to triazoles. Only 42.5% (17/40) C. tropicalis were susceptible/WT to all the triazoles, with 19 (47.5%) isolates NWT to posaconazole and 8 (20%) cross-resistant to triazoles. Among C. glabrata, 20 (55.6%) and 8 (22.2%) isolates were resistant/NWT to voriconazole and posaconazole, respectively, and 4 (10.3%) isolates were cross-resistant to triazoles. Isavuconazole was the most active triazole against common Candida isolates. Except for 2 isolates of C. glabrata cross-resistant to echinocandins which were also NWT to POS and defined as multidrug-resistant, echinocandins exhibit good activity against common Candida species. All isolates were WT to AMB. For less common species, Rhodotorula mucilaginosa exhibited high MICs to echinocandins and FLC, and 1 isolate of Trichosporon asahii showed high MICs to all the antifungals except AMB. Among triazole-resistant Candida isolates, ERG11 mutations were detected in 10/14 C. albicans and 6/23 C. tropicalis, while 21/23 C. tropicalis showed MDR1 overexpression. Overexpression of CDR1, CDR2, and SNQ2 exhibited in 14, 13, and 8 of 25 triazole-resistant C. glabrata isolates, with 5 isolates harboring PDR1 mutations and 2 echinocandins-resistant isolates harboring S663P mutation in FKS2. Overall, the CARST-fungi study demonstrated that although C. albicans remain the most predominant species, non-C. albicans species accounted for a high proportion. Triazole-resistance is notable among C. tropicalis and C. glabrata. Multidrug-resistant isolates of C. glabrata and less common yeast have been emerging.